A 3D-printed hierarchical porous architecture of MOF@clay composite for rapid and highly efficient dye scavenging. (29th November 2022) - Far, Hossein Shahriyari; Najafi, Mina; Hasanzadeh, Mahdi; Rahimi, Rahmatollah
Abstract : A self-supported, highly porous, 3D-printed lattice structure containing a MOF@clay composite for the adsorption of organic dyes from wastewater was successfully constructed. Abstract : Recently, 3D printing technology has attracted increasing attention for various applications such as wastewater treatment. Herein, we describe the fabrication of the 3D-printed architecture of a highly porous metal–organic framework (MOF) and clay (MOF@clay) composite. The chromium-based MOF was hybridized with clay clusters via an in situ solvothermal reaction, followed by immobilization of MOF@clay composite within the 3D-printed architecture with a cross-shaped unit cell. In this design, the microporous MOF@clay composite with its superior specific surface area (4959 m 2 g −1 ) significantly enhanced the efficiency of the 3D-printed architecture. As the results of MO dye adsorption experiments showed, the removal efficiency of the 3D-MOF@clay architecture was as high as 80% at pH = 4 for a contact time of 60 min. Moreover, the adsorption study indicates that the rapid adsorption and follows the Langmuir isotherm. The free-standing and easily recyclable 3D-MOF@clay architecture exhibits a fast, efficient and sustainable adsorption performance, which provides new insights for the rational design and fabrication of next-generation adsorbents for the removal of organic pollutants.